2017
DOI: 10.1037/rel0000101
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking self-transcendent positive emotions and religion: Insights from psychological and biblical research.

Abstract: At the heart of many religious and spiritual traditions is the aspiration to transcend the self to achieve a sense of connectedness with the world and/or with a Higher Power and to serve the greater good. Recent research suggests that the emergence of such self-transcendence can be facilitated by specific uplifting emotions termed self-transcendent positive emotions (STPEs); STPEs are short, positive responses to witnessing instances of beauty or good outside the self. The author reviews the defining character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 71 publications
1
30
0
Order By: Relevance
“…Using a similar longitudinal experimental design (i.e., 6-week meditation workshops, daily reports of positive emotions) we found that a common genetic variant associated with oxytocin signaling predict the degree to which mid-aged participants reported positive affect in response to loving-kindness meditation (Isgett, Algoe, Boulton, Way, & Fredrickson, 2016). In another study (Van Cappellen, Way, Isgett, & Fredrickson, 2016), we found that dual-blind administration of exogenous oxytocin vs. a placebo increased mid-aged men's positive affective responses – assessed with both implicit and explicit measures – to an initial 20-minute introduction to meditation, with effects especially evident for meaningful and self-transcendent affective experiences, such as gratitude and awe (Van Cappellen, in press). Future work is needed to investigate whether the oxytocin system influences positive affective responses to health behaviors other than meditation.…”
Section: Evidence For the Upward Spiral Theory's Outer Loop: Modifiabmentioning
confidence: 98%
“…Using a similar longitudinal experimental design (i.e., 6-week meditation workshops, daily reports of positive emotions) we found that a common genetic variant associated with oxytocin signaling predict the degree to which mid-aged participants reported positive affect in response to loving-kindness meditation (Isgett, Algoe, Boulton, Way, & Fredrickson, 2016). In another study (Van Cappellen, Way, Isgett, & Fredrickson, 2016), we found that dual-blind administration of exogenous oxytocin vs. a placebo increased mid-aged men's positive affective responses – assessed with both implicit and explicit measures – to an initial 20-minute introduction to meditation, with effects especially evident for meaningful and self-transcendent affective experiences, such as gratitude and awe (Van Cappellen, in press). Future work is needed to investigate whether the oxytocin system influences positive affective responses to health behaviors other than meditation.…”
Section: Evidence For the Upward Spiral Theory's Outer Loop: Modifiabmentioning
confidence: 98%
“…The effect of PES on compassion through common humanity is also consistent with a model proposed by Valdesolo and DeSteno (2011), which posits that synchronous movements may serve as a cooperation-enhancing mechanism, seemingly binding individuals together into a larger whole and, thus, facilitating reciprocal empathic and altruistic responses among them. There is also evidence indicating that collective synchrony increases willingness to help an out-group member as well as pro-sociality towards out-group members more generally (Reddish et al 2016;Van Cappellen 2017). More specifically, understanding and embracing the principles of harmonized "sangha-based" mindfulness appears to facilitate identifying with a sense of global human identity (de Rivera and Carson 2015), and universality (Piedmont 2012), as well as increased motivation to participate in collective gatherings (Basabe et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to examine the relationship between the beneficial aspects of religion in conjunction with the ways in which religion may be detrimental to health and well-being. Sixth, as we discussed earlier, researchers have identified other psychological factors that may influence a sense of meaning in life, such as positive emotions (Van Cappellen, 2017). To more correctly specify the nature of the relationship between social aspects of religion and meaning in life, it is important to include more psychological factors in the analyses.…”
Section: Discussionmentioning
confidence: 99%